2004
DOI: 10.1016/j.sse.2003.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Accurate modeling of gate capacitance in deep submicron MOSFETs with high-K gate-dielectrics

Abstract: Gate capacitance of metal-oxide-semiconductor devices with ultra-thin high-K gate-dielectric materials is calculated taking into account the penetration of wave functions into the gate-dielectric. When penetration effects are neglected, the gate capacitance is independent of the dielectric material for a given equivalent oxide thickness (EOT). Our selfconsistent numerical results show that in the presence of wave function penetration, even for the same EOT, gate capacitance depends on the gate-dielectric mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Figure 2 shows the normalized capacitance in a DG MOSFET with T Si = 5 nm as a function of V G . It is remarkable that capacitance variation for the two values of m * (0.1m 0 and 0.7m 0 ) is 3% (greater than that obtained by [4] for bulk transistors) and therefore an accurate model of effective mass is needed.…”
Section: Double Gate Mosfetsmentioning
confidence: 87%
See 3 more Smart Citations
“…Figure 2 shows the normalized capacitance in a DG MOSFET with T Si = 5 nm as a function of V G . It is remarkable that capacitance variation for the two values of m * (0.1m 0 and 0.7m 0 ) is 3% (greater than that obtained by [4] for bulk transistors) and therefore an accurate model of effective mass is needed.…”
Section: Double Gate Mosfetsmentioning
confidence: 87%
“…According to [4], when the same effective mass is considered for both insulators, the charge centroid for the device with a high-κ insulator is lower than in the case with SiO 2 . However, here it is shown that when different effective masses are considered, the behavior can be the opposite.…”
Section: Double Gate Mosfetsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the serious technology difficulties related to using ultra-thin SiO2 layers as the gate dielectric, alternative high-k materials are being considered as replacement of SiO2. It has been shown recently that the gate C-V characteristics of high-k gate-dielectric MOSFETs are determined by the effects of wave function penetration into the dielectric material [2,3].…”
Section: Introductionmentioning
confidence: 99%